2009
DOI: 10.1007/s00122-009-1202-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a resistance gene Rpi-dlc1 to Phytophthora infestans in European accessions of Solanum dulcamara

Abstract: Initial screening of 14 Solanum dulcamara accessions enabled the identification of individuals resistant and susceptible to Phytophthora infestans. Crosses between contrasting genotypes resulted in three F2–BC1 populations segregating for resistance to late blight in a laboratory assay and under field conditions. Genetic profiling of one of these populations using 128 AFLP primers generated three markers linked to the resistant phenotype. Blast analysis of the sequenced markers resulted in a plausible gene pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Such approach has been applied in another distant Solanum relative -S. dulcamara that cannot be crossed with potato. Using intraspecific crosses two late blight resistance genes of this species have been mapped: Rpi-dlc1 to chromosome IX (Golas et al 2010) and Rpi-dlc2 to chromosome X (Golas et al 2012). What is interesting, mapping of Rpidlc2 has been difficult due to the fact that in the mapping population both Rpi-dlc1 and Rpi-dlc2 were segregating and their phenotypic effects have been overlapping which is similar to the situation in our population B.…”
Section: Fig 1 Virulence Of 48 P Infestans Isolates On a Set Of Blsupporting
confidence: 63%
“…Such approach has been applied in another distant Solanum relative -S. dulcamara that cannot be crossed with potato. Using intraspecific crosses two late blight resistance genes of this species have been mapped: Rpi-dlc1 to chromosome IX (Golas et al 2010) and Rpi-dlc2 to chromosome X (Golas et al 2012). What is interesting, mapping of Rpidlc2 has been difficult due to the fact that in the mapping population both Rpi-dlc1 and Rpi-dlc2 were segregating and their phenotypic effects have been overlapping which is similar to the situation in our population B.…”
Section: Fig 1 Virulence Of 48 P Infestans Isolates On a Set Of Blsupporting
confidence: 63%
“…R genes conferring resistance to late blight, Rpi-moc1a.k.a. Rpi-mcq1 (Smilde et al 2005), Rpi-vnt1.1 Pel et al 2009), Rpi-phu1 (Śliwka et al 2006, Rpi-dlc1 (Golas et al 2010) and R8 (Jo et al 2011) have been reported in a similar position as dPI09c on the long arm of chromosome 9 in potato relatives. In the published sequence of the potato (DM) genome, nine Rpi-vnt1-like genes are present in the superscaffold PGSC0003DMB000000339, which in addition to the Rpi-vnt1-like genes contains other NBS-LRRlike genes.…”
Section: Discussionmentioning
confidence: 78%
“…However, efforts to use these markers in oat have not yet produced a consensus map, in which all linkage groups are assigned to the expected 21 oat chromosomes. AFLP markers have been associated with resistance genes in several species, including wheat (Weng and Lazar 2002;Randhawa et al 2009), tomato (Giovanni et al 2004;Golas et al 2010), maize (Duble et al 2003;Chen et al 2004;Liu et al 2009), canola (Kaur et al 2009), and radish (Kamei et al 2010). In the present study, the AFLP molecular markers U8PM22 and U8PM25, developed by Locatelli et al, were associated with the Pc68 gene.…”
Section: Mapping Analysismentioning
confidence: 98%